A Comprehensive Bibliometric Review of Business Model Innovation in Entrepreneurial Economics Literature - Loso Judijanto; Antoni Antoni; Firdaus Firdaus; Megha Sakova; Dang Panagaman Tamba (The Es Economics and Entrepreneurship, 2026)
This study provides a comprehensive bibliometric review of Business Model Innovation (BMI) within the field of entrepreneurship economics, aiming to map the intellectual structure, research evolution, and emerging trends. Using the Scopus database, relevant publications from 2000 to 2026 were systematically collected and analyzed through bibliometric techniques, including co-authorship, citation, and keyword co-occurrence analysis, with visualization supported by VOSviewer. The results reveal a significant increase in BMI-related publications, particularly in the last decade, indicating growing scholarly attention to innovation-driven entrepreneurship. The author collaboration network shows a fragmented structure, suggesting limited integration across research communities. Country analysis highlights the dominance of developed economies, while contributions from developing regions remain relatively low. Citation analysis identifies foundational works related to business ecosystems and value creation, alongside emerging studies focusing on digital transformation, sustainability, and circular economy. Furthermore, keyword analysis demonstrates that BMI research is centered around innovation and economics, with recent trends shifting toward sustainability and digitalization. This study contributes by offering a structured overview of BMI literature, identifying research gaps, and providing directions for future research, particularly in interdisciplinary integration and the inclusion of diverse economic contexts.